Fragmented-brand consumerism on TikTok: The advertising impact on generation Alpha - Cortés-Quesada, Jose Antonio (2025)
TikTok’s rapid rise and popularity pose challenges to young users. This study applies a mixed-methods approach to examine the impact of advertising on generation Alpha through the analysis of 500 child-targeted videos and the Delphi method with 12 psychologists. The quantitative content analysis reveals that TikTok’s short, dynamic videos cater to children’s preferences, with significant gender-based segmentation: boys are more frequently exposed to political and sports content, while girls encounter more beauty and lifestyle content. Experts indicate that the app’s fragmented, fast-paced content diminishes attention spans and fosters addictive purchasing behaviors among the youngest audience. Furthermore, the subtle nature of influencer-driven advertising complicates children’s ability to identify promotional content, potentially heightening their consumerism and anxiety. These findings underscore the urgent need for enhanced parental supervision, ethical advertising practices, and transparent regulatory measures to protect generation Alpha’s psychological well-being from the effects of fragmented brand consumerism.